1993
DOI: 10.1002/cne.903350104
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the suprachiasmatic nucleus to stress‐related areas in the rat hypothalamus: A light and electron microscopic study

Abstract: The purpose of the present study was to investigate the sites in the hypothalamus where the suprachiasmatic nucleus (SCN) may influence corticosteroid secretion. In spite of the well established, SCN-mediated, daily rhythms in adrenocorticotrophic hormone (ACTH) and corticosteroid secretion, previous studies determining the projections of the suprachiasmatic nucleus failed to illustrate direct connections with corticotrophin-releasing hormone neurons (CRH). In order to identify where in the central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 26 publications
7
95
0
2
Order By: Relevance
“…The early onset of the stimulatory SCN input (i.e., between CT2 and CT6), as revealed by our timed VP antagonist infusions, would agree with the often-reported phaseadvanced rhythms of CRH and ACTH compared with that of corticosterone (Szafarczyk et al, 1980;Graf et al, 1988;Carnes et al, 1989;Owens et al, 1990;Kwak et al, 1992;Cai and Wise, 1996) and the elevated daytime levels of GRP mRNA in the SCN (Zoeller et al, 1992;Inouye et al, 1993;Inouye and Shibata, 1994). Because VP-, VIP-, and GRP-containing SCN fibers display clearly separated innervation patterns of the PVN/DMH subdivisions (Buijs et al, 1993b;Kalsbeek et al, 1993), a differentiated control of ACTH and corticosterone release by SCN efferences is certainly possible. However, as yet no conclusive anatomical data are available to back up the dual control pattern of ACTH and corticosterone release as proposed in the foregoing.…”
Section: Discussionsupporting
confidence: 87%
“…The early onset of the stimulatory SCN input (i.e., between CT2 and CT6), as revealed by our timed VP antagonist infusions, would agree with the often-reported phaseadvanced rhythms of CRH and ACTH compared with that of corticosterone (Szafarczyk et al, 1980;Graf et al, 1988;Carnes et al, 1989;Owens et al, 1990;Kwak et al, 1992;Cai and Wise, 1996) and the elevated daytime levels of GRP mRNA in the SCN (Zoeller et al, 1992;Inouye et al, 1993;Inouye and Shibata, 1994). Because VP-, VIP-, and GRP-containing SCN fibers display clearly separated innervation patterns of the PVN/DMH subdivisions (Buijs et al, 1993b;Kalsbeek et al, 1993), a differentiated control of ACTH and corticosterone release by SCN efferences is certainly possible. However, as yet no conclusive anatomical data are available to back up the dual control pattern of ACTH and corticosterone release as proposed in the foregoing.…”
Section: Discussionsupporting
confidence: 87%
“…Early tracing studies examining the output of the DMH have shown that its projections are mainly limited to hypothalamic structures (34). This observation, together with data showing that the DMH receives an important input from the nucleus of the solitary tract, arcuate, and SCN (35)(36)(37), supports the view that the DMH is essential for the distribution of metabolic and circadian signals within the hypothalamus. The present results emphasize the important role of the DMH because they show that, under normal conditions, the DMH has the capacity to "silence" the SCN to allow locomotor activity at a moment of the day when such behavior is normally prevented by the activity of the SCN.…”
Section: Faa Is Lost After Lesion Of the Dmh But Reappears After Amentioning
confidence: 67%
“…In addition, there is also evidence for GABAergic projections from the DMH to the PVN (Boudaba et al, 1996). Because the DMH is also a target area for SCN projections (Watts et al, 1987;Buijs et al, 1993), the SCN might use both direct and indirect GABAergic projections to the preautonomic neurons in the PVN to control basal plasma glucose concentrations, implying that SCN projections to the GABAergic DMH neurons are stimulatory. In addition to the SCN and DMH, GABAergic inputs from other sources may restrain the activity of preautonomic PVN neurons controlling HGP.…”
Section: Discussionmentioning
confidence: 99%